Two Penniless Princesses - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2001)
"Two Penniless Princesses" by Charlotte M. Yonge is a historical novel set in the late 19th century. The story revolves around two young princesses, Eleanor and Jean Stewart, who face the challenges of their royal status within the troubled Scottish court. Captured and confined in Dunbar Castle, they yearn for freedom and the joy of life beyond the dreariness of their surroundings, particularly longing for their sister Margaret, who has been married into the French court. The opening of the novel introduces us to the sisters in Dunbar Castle, where they share dreams of escape and adventure. Amid the bleakness of their captivity, they are preoccupied with thoughts of royalty and love, and their desire to reunite with Margaret drives the narrative. The sisters are expressed as strong characters; Eleanor is wistful and imaginative, while Jean is practical and steadfast. Their discussions reveal their hopes and frustrations, as they navigate the dangers of their situation, including threats from warlike nobles eager for connections with royalty. As the story begins, they are on the cusp of a significant journey towards their destiny, filled with anticipation and trepidation. (This is an automatically generated summary.)
Release date is 2001-12-01
Produced by Sandra Laythorpe, and David Widger
Keywords: Knights and knighthood -- Fiction; France -- History -- Charles VII, 1422-1461 -- Fiction; Chivalry -- Fiction; Inheritance and succession -- Fiction; Conduct of life -- Fiction; Siblings -- Fiction; Prisoners -- Fiction; Princesses -- Fiction; Marriage -- Fiction; Scotland -- History -- James II, 1437-1460 -- Fiction